Contribution of Large Pig for Renal Ischemia-Reperfusion and Transplantation Studies: The Preclinical Model. (3rd March 2011) - Giraud, S.; Favreau, F.; Chatauret, N.; Thuillier, R.; Maiga, S.; Hauet, T.
Abstract : Animal experimentation is necessary to characterize human diseases and design adequate therapeutic interventions. In renal transplantation research, the limited number of in vitro models involves a crucial role for in vivo models and particularly for the porcine model. Pig and human kidneys are anatomically similar (characterized by multilobular structure in contrast to rodent and dog kidneys unilobular). The human proximity of porcine physiology and immune systems provides a basic knowledge of graft recovery and inflammatory physiopathology through in vivo studies. In addition, pig large body size allows surgical procedures similar to humans, repeated collections of peripheral blood or renal biopsies making pigs ideal for medical training and for the assessment of preclinical technologies. However, its size is also its main drawback implying expensive housing. Nevertheless, pig models are relevant alternatives to primate models, offering promising perspectives with developments of transgenic modulation and marginal donor models facilitating data extrapolation to human conditions.